Early-onset type 2 diabetes in a Mexican survey: results from the National Health and Nutrition Survey 2006 Diabetes tipo 2 de inicio temprano en una encuesta nacional: resultados de la Encuesta Nacional de Salud y Nutrición 2006 - Aída Jiménez-Corona; Rosalba Rojas; Francisco J Gómez-Pérez; Carlos A Aguilar-Salinas (Salud Pública de México, 2010)
OBJECTIVE: To describe the characteristics of patients with type 2 diabetes diagnosed before age 40 (early-onset type 2 diabetes) identified in a nation-wide, population-based study. MATERIALS AND METHODS: The survey was done in Mexico during 2006. Medical history, anthropometric and biochemical measurements were obtained in every subject. RESULTS: Cases diagnosed before (n=181) and after age 40 (n=659) were included. Early-onset type 2 diabetes was present in 13.1% of the previously diagnosed, 30.3% of the cases identified during the survey and 21.5% of the whole population with diabetes. These individuals had a greater prevalence of obesity and hypertriglyceridemia compared to the cases diagnosed after age 40. CONCLUSIONS: Early-onset type 2 diabetes was present in 21.5 % of patients with type 2 diabetes in Mexico. Close to 70% of them were obese or overweight and had the clinical profile of the metabolic syndrome. OBJETIVO: Describir las características de los pacientes con diabetes diagnosticados antes de los 40 años en una encuesta representativa de la población mexicana. MATERIAL Y MÉTODOS: La encuesta fue realizada en México durante 2006. Se registró la historia médica, mediciones antropométricas y bioquímicas de los participantes. RESULTADOS: Se incluyeron casos diagnosticados antes (n=181) y después (n=659) de los 40 años. La diabetes tipo 2 de inicio temprano está presente en 13.1% de los casos previamente diagnosticados, 30.3% de los identificados durante la encuesta y en 21.5% de la población total con diabetes. En los casos diagnosticados antes de los 40 años hay una prevalencia mayor de obesidad e hipertrigliceridemia que en los diagnosticados después de los 40. CONCLUSIONES: La diabetes de aparición temprana está presente en 21.5% de los casos con diabetes en México. Setenta por ciento de ellos tenían un peso mayor al saludable y tenían el perfil clínico del síndrome metabólico.